EFEKTIVITAS FUNGI MIKORIZA ARBUSKULAR DENGAN PROVENAN JARAK PAGAR PADA CEKAMAN KEKERINGAN - Lapanjang, Iskandar M.; Purwoko, Bambang S.; Hariyadi, Hariyadi; Wilarso, Sri; Melati, Maya (JURNAL AGROTROPIKA, 2011)
The study was conducted to investigate the effectiveness of Arbuscular Mycorrhizae Fungi (AMF) to make a symbiosis with physic nuts under drought stress condition. The experiment was carried out in plastic house in Kota Palu, Central Sulawesi, from October 2008 to January 2009. The experiment used completely randomized block design with 3 factors and 3 replications. The first factor was AMF type i.e. without AMF, AMF Glomus sp-1p, AMF Acaulospora sp-1p, and mixture of Glomus sp-1p and Acaulospora sp-1p. The second factor was the provenances of physic nut i.e. Palu, NTB, IP-1A, and IP-1P. The third factor was soil water content i.e. 80 and 40% of field capacity. The results showed that the application of AMF resulted in better growth of all provenances especially ecotype IP-1P, which was sensitive to drought, compared to control (without AMF). At 40% field capacity, mixture of Glomus sp-1p and Acaulospora sp-1p. was more effective compared to single AMF in improving plant growth. The highest AMF infection was found in ecotype Palu inoculated with mixture of Glomus sp-1p and Acaulospora sp-1p. Key words: infection level, Glomus, Acaulospora